From Skills to Transformative Entrepreneurial Capacity: An Agenda for Educating the Next Generation in the Digital Agri-Industry Innovation Ecosystem - Chen, Si; Sun, Yuqing; Shokrollahi, Foad; Sun, Lipeng (John Wiley & Sons, 2026)
Entrepreneurship education in agri-industry is being asked to prepare learners for a sector increasingly organised through platforms, data infrastructures, and traceability systems. Yet much current provision remains centred on a skills paradigm focused on tool use, operational tips, and short-term performance. This paper argues that such an approach is no longer sufficient for a sector shaped by bio-temporal constraints, quality heterogeneity, perishability, logistics dependence, and compliance burdens. It proposes transformative entrepreneurial capacity (TEC) as the central educational objective for sustainable agri-industry transitions. TEC is understood as the capacity to turn digitally mediated opportunities and constraints into viable, inclusive, and environmentally credible upgrading pathways. The paper's main contribution is to reframe entrepreneurship education in agri-industry as ecosystem-embedded capability formation rather than as the delivery of discrete digital skills. To make this argument operational, it introduces a concise CPAD–Ecosystem–Transition framework that places educational design—Curriculum, Pedagogy, Assessment, and Delivery/governance—at the centre of capability formation within the agri-industry innovation ecosystem. On this basis, the paper identifies four priority themes for future research: curricularising TEC under bio-temporal constraints; designing pedagogies for distributed learning environments across farms, cooperatives, extension and platforms; developing assessments and credentials that evidence TEC without creating new exclusions; and examining delivery and governance models that coordinate multi-actor education while protecting inclusion. The agenda calls for comparative and mechanism-focused research to assess how educational design can support inclusive and sustainable upgrading in digitally mediated agri-industry.
Keywords: digitalisation; entrepreneurship education; innovation ecosystem; platform and metric governance; transformative entrepreneurial capacity (TEC); fi=Matemaattiset tieteet|en=Mathematics|